CAFFEIN LEVELS IN GREEN TEA BAGS - Riong Seulina Panjaitan; Risty Setyati Ashari; Saiful Anwar; Nurul Asfia; Silvy Widya Rahmi; Marisa Tamara Sari (Indonesian Journal of Pharmaceutical Research, 2022)
Caffeine is known to have a pharmacological effect, namely as a stimulant for the central nervous system and metabolism, besides that it can be used for treatment in reducing physical overload and can also increase alertness levels. This study aims to determine the caffeine content in 25 grams (10 bags of green tea bags) from 3 different packaging brands. Extraction of caffeine from green tea bags was carried out using the maceration method, and recrystallization of the caffeine content with hot acetone, then titration of ligroin(n-hexane) to obtain pure crystals. The caffeine obtained from 3 samples, namely sample A obtained 0.099% sample B obtained 0.088% sample C obtained 0.094 % and all samples in the safe category did not exceed SNI is 50 mg/serving.